(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In recent years, there has been a growing interest in the health benefits of plant-based diets, both from the perspective of individual well-being and public health. This clinical review aims to explore the numerous advantages associated with adopting a plant-based diet while presenting evidence from various studies conducted on this subject.